The cellular composition of the tumor microenvironment is an important marker for predicting therapeutic efficacy in breast cancer - Dou, Tingyao; Li, Jing; Zhang, Yaochen; Pei, Wanru; Zhang, Binyue; Wang, Bin; Wang, Yanhong; Jia, Hongyan (Frontiers in Immunology, 2024)
At present, the incidence rate of breast cancer ranks first among new-onset malignant tumours in women. The tumour microenvironment is a hot topic in tumour research. There are abundant cells in the tumour microenvironment that play a protumor or antitumour role in breast cancer. During the treatment of breast cancer, different cells have different influences on the therapeutic response.And after treatment, the cellular composition in the tumour microenvironment will change too. In this review, we summarize the interactions between different cell compositions (such as immune cells, fibroblasts, endothelial cells, and adipocytes) in the tumour microenvironment and the treatment mechanism of breast cancer. We believe that detecting the cellular composition of the tumour microenvironment is able to predict the therapeutic efficacy of treatments for breast cancer and benefit to combination administration of breast cancer.